Eye Movement Monitoring Reveals Differential Influences of Emotion on Memory - Riggs, Lily; McQuiggan, Douglas A.; Anderson, Adam K.; Ryan, Jennifer D. (Frontiers in Psychology, 2010)
Research shows that memory for emotional aspects of an event may be enhanced at the cost of impaired memory for surrounding peripheral details. However, this has only been assessed directly via verbal reports which reveal the outcome of a long stream of processing but cannot shed light on how/when emotion may affect the retrieval process. In the present experiment, eye movement monitoring was used as an indirect measure of memory as it can reveal aspects of online memory processing. For example, do emotions modulate the nature of memory representations or the speed with which such memories can be accessed? Participants viewed central negative and neutral scenes surrounded by three neutral objects and after a brief delay, memory was assessed indirectly via eye movement monitoring and then directly via verbal reports. Consistent with the previous literature, emotion enhanced central and impaired peripheral memory as indexed by eye movement scanning and verbal reports. This suggests that eye movement scanning may contribute and/or is related to conscious access of memory. However, the central/peripheral tradeoff effect was not observed in an early measure of eye movement behavior, i.e. participants were faster to orient to a critical region of change in the periphery irrespective of whether it was previously studied in a negative or neutral context. These findings demonstrate emotion’s differential influences on different aspects of retrieval. In particular, emotion appears to affect the detail within, and/or the evaluation of, stored memory representations, but it may not affect the initial access to those representations.